GenVec Vaccine Technology Enters First HIV Human Therapeutic Clinical Trials at Vaccine Research Center at NIH (Business Wire, 2006)
Statements herein relating to future financial or business performance, conditions or strategies and other financial and business matters, including expectations regarding future programs and studies, are forward-looking statements within the meaning of the Private Securities Litigation Reform Act. GenVec cautions that these forward-looking statements are subject to numerous assumptions, risks and uncertainties, which change over time. Factors that may cause actual results to differ materially from the results discussed in the forward-looking statements or historical experience include risks relating to the early stage of GenVec's product candidates under development; uncertainties relating to clinical trials; the timing and content of future U.S. Food and Drug Administration regulatory actions with respect to GenVec, its product candidates, or collaborators, risks relating to the commercialization, if any, of GenVec's proposed product candidates (such as marketing, regulatory, patent, product liability, supply, competition and other risks); dependence on the efforts of third parties; dependence on intellectual property; and risks that we may lack the financial resources and access to capital to fund our operations. Further information on the factors and risks that could affect GenVec's business, financial conditions and results of operations, are contained in GenVec's filings with the U.S. Securities and Exchange Commission (SEC), which are available at www.sec.gov.